Marketing Strategy of Star Fruit (Averhoa bilimbi L) in Tulungagung District - Suparno, Suparno (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2019)
Star fruit ( Averhoa bilimbi L ) is widely planted in Tulungagung Regency, East Java, because according to its agro-climate, it is easy to plant and maintain, and also easy to market. The research objectives are 1. Analyzing the condition of internal and external factors in the marketing of star fruit in Tulungagung Regency, and 2. Determining the strategy that needs to be done in marketing star fruit in Tulungagung Regency. The study was conducted in Tulungagung Regency, the data obtained were analyzed by the SWOT method, then a strategy was established. Based on the results of the analysis it can be concluded that the star fruit marketing strategy in Tulungagung Regency is an SO strategy that is to use power to take advantage of opportunities, its activities are: 1. Specific guidance for star fruit farmers; 2. Increase production to meet market needs; 3. Policy for guiding and processing star fruit; 4. Coordinating distributors with transportation services; 5. Priority for exemplary farmers; 6. Utilization of the local market